2023
DOI: 10.1002/fsn3.3231
|View full text |Cite
|
Sign up to set email alerts
|

lncRNA TINCR knockdown inhibits colon cancer cells via regulation of autophagy

Abstract: The present study aimed to evaluate the effects of long noncoding (lnc)RNA TINCR ubiquitin domain containing (TINCR) on the development of colon cancer, and the specific underlying mechanisms. The present study used adjacent healthy and cancer tissues obtained from patients with colon cancer and measured lncRNA TINCR expression using reverse transcription‐quantitative (RT‐q) PCR and in situ hybridization assays. Moreover, associations between lncRNA TINCR and clinicopathology and prognosis were also investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…There are some studies on the number of LncRNA gene polymorphisms associated with various tumors and abnormal expression in many human cancers that have revealed no significant link between their polymorphism and the likelihood of recurrent miscarriage, such as TINCR gene rs2288947 (Y. Liu et al, 2018 (Xu et al, 2023) (Icduygu et al, 2022)(W. , and TOX3 gene that is linked with numerous disorders such as cancer of the pulmonary system, ovarian cancer, breast cancer and polystatic ovarian syndrome (Latif et al, 2010)(W. M. Cao et al, 2016)(X. Zhang et al, 2013)(Gao et al, 2018)(L. Chen et al, 2017 (Bruni et al, 2022).…”
Section: Genetic Susceptibility To Recurrent Miscarriagementioning
confidence: 99%
“…There are some studies on the number of LncRNA gene polymorphisms associated with various tumors and abnormal expression in many human cancers that have revealed no significant link between their polymorphism and the likelihood of recurrent miscarriage, such as TINCR gene rs2288947 (Y. Liu et al, 2018 (Xu et al, 2023) (Icduygu et al, 2022)(W. , and TOX3 gene that is linked with numerous disorders such as cancer of the pulmonary system, ovarian cancer, breast cancer and polystatic ovarian syndrome (Latif et al, 2010)(W. M. Cao et al, 2016)(X. Zhang et al, 2013)(Gao et al, 2018)(L. Chen et al, 2017 (Bruni et al, 2022).…”
Section: Genetic Susceptibility To Recurrent Miscarriagementioning
confidence: 99%
“…Colorectal cancer, is a common malignant tumour worldwide, with >1 million new cases each year, accounting for ~10% of new cancer cases, and a mortality rate accounting for 9.4% of all cancer deaths, making it a focus of attention in the field of public health (1,2). Despite considerable progress in multimodal treatment approaches, including precision surgery and tailored chemoradiotherapy, achieving long-term survival and effective disease management poses significant challenges for patients with advanced or highly invasive forms of this cancer (3).…”
Section: Introductionmentioning
confidence: 99%
“…Long non-coding RNAs (lncRNAs) are non-coding RNAs with a length of >200 nt, which cannot encode proteins but can regulate gene expression through transcriptional, post-transcriptional and epigenetic mechanisms (4). Relevant studies demonstrated that the lncRNA tissue differentiation-inducing non-protein coding RNA (TINCR) participates in tumor progression and is abnormally expressed in various tumor tissues (5)(6)(7)(8). TINCR plays an inhibitory role in prostate cancer (5), whereas it plays a promoting role in other types of tumors including NSCLC, HCC and colon cancer, TINCR is closely correlation with poor prognosis in NSCLC and colon cancer and TINCR overexpression also stimulated cancer cells biological activities including cell proliferation, invasion and migration (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…Relevant studies demonstrated that the lncRNA tissue differentiation-inducing non-protein coding RNA (TINCR) participates in tumor progression and is abnormally expressed in various tumor tissues (5)(6)(7)(8). TINCR plays an inhibitory role in prostate cancer (5), whereas it plays a promoting role in other types of tumors including NSCLC, HCC and colon cancer, TINCR is closely correlation with poor prognosis in NSCLC and colon cancer and TINCR overexpression also stimulated cancer cells biological activities including cell proliferation, invasion and migration (6)(7)(8). However, the expression of lncRNA TINCR in cervical cancer and its association with the prognosis of patients, as well as its mechanisms of action in cervical cancer occurrence and development remain unclear.…”
Section: Introductionmentioning
confidence: 99%